From Theory to Practice: Enhancing Public Administration Leaders Capacities through collaborative training programs - Ferraz, David (From Theory to Practice: Enhancing Public Administration Leaders Capacities through collaborative training programs, 2024)
I. Education and Training in Public Administration The training of public leaders is a critical theme for the performance of Public Administration, particularly in responding to contemporary challenges. It constitutes a critical success factor for governance and the achievement of Sustainable Development Goals (SDGs). Public leaders serve as the bridge between political power and Public Administration, acting as agents and catalysts for change. Their impact—whether positive or negative—directly affects the performance of public organizations and, consequently, public policies. Given these reasons, investment in training and personal development policies assumes particular importance. These policies not only qualify public leaders for their multifaceted roles on VUCA contexts but also contribute to creating a more homogeneous management language and model within the context of network collaboration and necessary alignment among organizations to address wicked problems, whether in the context of New Public Governance (NPG) or neo-Weberianism. In this article, we delve into the changes introduced to the leadership training model, aiming to adapt and reorient it to meet contemporary needs and challenges on VUCA context. To achieve this, we employ a mixed-method approach, combining literature review, document analysis, mega-tendencies analyse, expert interviews, and focus groups. With this paper we contribute do the discussion of effective instructional strategies needed, analyse the challenges posed on PA training and discuss possible solutions to enhance the capacity of public leaders on an ongoing approach. The outcome of this work has led to a legal framework modification of the leadership training in Portugal. This adjustment addresses identified gaps placing a stronger focus on managers. The training now includes on each topic contextualized masterclasses, individual assignments, and group discussions for each topic covered based on active pedagogies. The model has been designed holistically, allowing multiple entities to participate in a consortium. It aligns with formal education with partially recognizes trainings at the university level (Master’s degree) in the field of Public Administration, with credits measured in ECTS units but in accordance to the instructional strategies for developing competencies defined by the created consortium on PA training (National Institute of Administration and PA Universities). The results achieved so far demonstrate a paradigm shift in training with new methodologies and active pedagogies on the core of the training process, fostering peer sharing and learning. Preliminary assessments reveal increased satisfaction among public managers and public organizations, along with a heightened perception of professionalization and return on the investment for the creation of public value.